CLASH: extreme emission line galaxies and their implication on selection of high-redshift galaxies - Huang, Xingxing; Bartelmann, Matthias (Arxiv, 2014)
We utilize the CLASH (Cluster Lensing And Supernova survey with Hubble) observations of 25 clusters to search for extreme emission-line galaxies (EELGs). The selections are carried out in two central bands: F105W (Y105) and F125W (J125), as the flux of the central bands could be enhanced by the presence of [O III] 4959, 5007 at redshift of about 0.93-1.14 and 1.57-1.79, respectively. The multi-band observations help to constrain the equivalent widths of emission lines. Thanks to cluster lensing, we are able to identify 52 candidates down to an intrinsic limiting magnitude of 28.5 and to a rest-frame [O III] 4959,5007 equivalent width of about 3737 angstrom. Our samples include a number of EELGs at lower luminosities that are missed in other surveys, and the extremely high equivalent width can be only found in such faint galaxies. These EELGs can mimic the dropout feature similar to that of high redshift galaxies and contaminate the color-color selection of high redshift galaxies when the S/N ratio is limited or the band coverage is incomplete. We predict that the fraction of EELGs in the future high redshift galaxy selections cannot be neglected.